IMPLEMENTASI KEBIJAKAN PENGELOLAAN KEBERSIHAN DI KECAMATAN MALALAYANG KOTA MANADO - Pinatik, Levin Philips (JURNAL ADMINISTRASI PUBLIK, 2018)
The purpose of this study is to explain the process of implementing hygiene management policies in Malalayang sub-district, Manado. This study uses a qualitative descriptive method, which is to explain or describe descriptively about how and why various variants or factors related to the implementation of hygiene management policies in Malalayang sub-district.The results showed that 1. The enactment of the Mayor of Manado regulation No. 13 of 2016 concerning the delegation of authority over hygiene management to the Malalayang sub-district of Manado City, when viewed from aspects of standard policies and targets, resources, communication, characteristics, social, economic, political and aspects of involvement attitudes or dispositions are appropriate and appropriate application indicated by the results of interviews of all informants who argued that the level of perception was good and satisfied with the performance of the Malalayang District government along with its staff in hygiene management, 2. Implementation of hygiene management policies in Malalayang sub-district when viewed from five aspects namely policy standards and targets, communication, characteristics, involvement of the social, economic, political environment as well as aspects of attitudes or dispositions, the implementation has been effective and good, but when viewed from the aspect of resources, management of cleanliness is still felt to be not efficient enough from in terms of the time of completion and still not suitable as expected to compensate for the large volume of waste produced, due to the limited resources available such as: the need for additional facilities for garbage transportation vehicles and daily freelancers (THL), there are still long distances for every facility and infrastructure for hygiene management in urban villages. Keywords: Policy Implementation, Hygiene, Management.